Impact of certification courses on performance of employees in Information Technology Sector - Yamini Patel (International Journal of Advanced Science and Technology, 2020)
With technology moving at a rapid pace it has become essential for an employer as well as employee to adapt to the change and when it comes to enhancement of employee, apart from regular training, an individual also has access to various courses that provide knowledge and learning for the same. Certification courses are the courses that have a shorter span compared to the regular learning methodology and is aimed at providing the right competency and skill to the person who pursues the certification for the topic/domain one has opted for. With the increasing competition in various areas like engineering, IT, management etc. getting a certification provides the employee benefit of showcasing their learning in their deliverables and allow them to provide their proficiency. This study attempts to study the relationship between the certification courses taken by an employee and their performance in the IT sector. The intent behind this research is to understand if the certifications completed by employees have an impact on their performance. According to secondary results a certification course does provide benefits to the employee but does it drive an employee’s performance for IT employees in India needs to be researched upon.This study is based on research done on similar topics with secondary data focusing more on online certifications, courses and primary data collected from IT professionals in India involving software developers and testers.Keywords: Information Technology,certification courses, employee performance